2022
DOI: 10.1186/s12909-022-03917-3
|View full text |Cite
|
Sign up to set email alerts
|

Online flipped classroom with team-based learning promoted learning activity in a clinical laboratory immunology class: response to the COVID-19 pandemic

Abstract: Background Given the rapid development of clinical immunology technologies, students majoring in laboratory medicine should master the technological principles and application of clinical laboratory immunology. However, many are required to take online courses due to COVID-19 restrictions, which highlights the need to revisit teaching strategies. Recently, various medical education courses (such as Biochemistry, Physiology, etc.) have implemented the flipped classroom (FC) and team-based learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The favorable scores within the cognitive presence domain for the online FC tutorial are consistent with findings from other FC-oriented studies, both for in-person and online FC compared to traditional learning formats. 3,6,[9][10][11] Students reported feeling more engaged in discussing ideas, more able to identify relevant points from the thyroid case vignettes, and more ready to apply learning concepts than after online lectures. This is perhaps not too surprising given the inherent nature of the FC model in which students have already reviewed resources and video recordings before class and are primed to dive into extended discussion on class arrival.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The favorable scores within the cognitive presence domain for the online FC tutorial are consistent with findings from other FC-oriented studies, both for in-person and online FC compared to traditional learning formats. 3,6,[9][10][11] Students reported feeling more engaged in discussing ideas, more able to identify relevant points from the thyroid case vignettes, and more ready to apply learning concepts than after online lectures. This is perhaps not too surprising given the inherent nature of the FC model in which students have already reviewed resources and video recordings before class and are primed to dive into extended discussion on class arrival.…”
Section: Discussionmentioning
confidence: 99%
“…In general, exam performance has been observed to be stronger after online FC modalities compared with online lectures. 10,11,13 On the other hand, a recent study examining online FC versus in-person FC formats in a physical therapy course demonstrated that exam performance and total course grade were similar between the two formats. 29 Thus, in-person and online FC formats for our thyroid pathophysiology tutorial might have resulted in similar test performance as well.…”
Section: Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations